2015
DOI: 10.1111/birt.12166
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuturing or Skin Adhesives versus Suturing of the Perineal Skin After Childbirth: A Systematic Review

Abstract: Nonsuturing of the skin or the use of skin adhesives appears preferable in terms of pain. Nonsuturing could lead to more short-term skin separation when no adhesives are used, but there is no evidence for the clinical importance of skin separation. There is a need for studies with a follow-up of at least 6 months, in which pain is measured homogeneously and for studies comparing the use of skin adhesives with nonsuturing of the skin with the focus on long-term cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
3
14
0
5
Order By: Relevance
“…1 In an effort to reduce procedure-related morbidity and improve cosmesis, there have been various attempts to modify and improve the technique of episiotomy. 1,2 These range from the use of hyaluronidase injections to non-suturing of perineal skin. 3 However, data has been insufficient and a Cochrane review in 2000 described the need for prospective studies involving cosmetic results of perineal skin.…”
Section: Introductionmentioning
confidence: 99%
“…1 In an effort to reduce procedure-related morbidity and improve cosmesis, there have been various attempts to modify and improve the technique of episiotomy. 1,2 These range from the use of hyaluronidase injections to non-suturing of perineal skin. 3 However, data has been insufficient and a Cochrane review in 2000 described the need for prospective studies involving cosmetic results of perineal skin.…”
Section: Introductionmentioning
confidence: 99%
“…The current review showed that not suturing the skin caused less short-term and long-term pain compared with suturing the skin as well as an increased rate of skin separation. Skin adhesives caused less shortterm pain without a statistically significant increase of skin separation, as compared with the suturing group [14].…”
Section: Discussionmentioning
confidence: 82%
“…The reported complications of episiotomy closure were skin dehiscence, adhesive / suture detachment, perineal edema, severe pain, longer hospital stay, granuloma formation, local infection and dyspareunia. Many studies reported the similar complication rates of tissue adhesive [14] compared with suture methods. In our study, tissue adhesive group had 11%, while subcuticular group had 16% of complication rate.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Preservation of perineal integrity, 2 nd degree laceration rate, and laceration suture were similar to those of national studies (8)(9)(10) . Moreover, most lacerations were not sutured, following a tendency to adopt natural healing, which seems to contribute to the reduction of pain (25) . However, more evidence is needed to support this practice (26) .…”
Section: Discussionmentioning
confidence: 99%